Physical mapping of 14 new DNA markers isolated from the human distal Xp region - Wapenaar, Martin C.; Petit, Christine; Basler, E.; Ballabio, A.; Henke, Anja; Rappold, Gudrun; Paassen, H. M. B.; Blonden, L. A. J.; Ommen, G. J. B. (Genomics, 1992)
We have isolated 14 new DNA markers from the human Xpter-Xp21 region distal to the Duchenne muscular dystrophy gene by targeted cloning, employing two somatic cell hybrids containing this region as their sole human material. High-resolution physical localization of these markers within this region was obtained by hybridization to two mapping panels consisting of DNA from patients carrying various translocations and deletions in distal Xp. Five markers were assigned to the pseudoautosomal region where their position on the long-range map of this region was further determined by pulsed-field gel electrophoresis. The other nine markers map to the X-specific region. Informative TaqI restriction fragment length polymorphisms were observed for four loci. One of these represents a region-specific low-copy repeated element. These 14 new markers represent useful tools for the understanding of distal Xp deletion and translocation mechanisms and for the positional cloning of disease genes in the region.
Online 6 December 2004
Elektronische Reproduktion der Druck-Ausgabe
Gesehen am 31.03.2021